(untitled) (Journal of Applied Learning and Teaching, 2020)
Students are increasingly diverse, with traditional pedagogies and instructional approaches lacking effectiveness in engaging a variety of student cohorts. This study takes a behavioural approach to examining students in the classroom, seeking to better understand the relationships between authentic leadership, wellbeing, belonging, and engagement among students in an Australian Associate Degree program. This paper reports on a quantitative survey conducted at the beginning of a teaching period, with longitudinal data points expected as this cohort progresses. Preliminary findings are that while students’ self-reported authentic leadership scores had associated gains in their psychological wellbeing, and classroom belongingness and engagement, their informal influence played the largest role. This could indicate that supporting students to develop deeper psychological behavioural capabilities (such as self-awareness and sincerity) would have the potential to strengthen the relationship between authentic leadership and student outcomes, by supporting a self-reinforcing effect among the authentic leader behaviours.